Approximating biobjective minimization problems using general ordering cones - Arne Herzel; Stephan Helfrich; Stefan Ruzika; Clemens Thielen (Journal of Global Optimization, 2023)
This article investigates the approximation quality achievable for biobjective minimization problems with respect to the Pareto cone by solutions that are (approximately) optimal with respect to larger ordering cones. When simultaneously considering α-approximations for all closed convex ordering cones of a fixed inner angle~ γ∈π2,π, an approximation guarantee between~ αand~ 2αis achieved, which depends continuously on~ γ. The analysis is best-possible for any inner angle and it generalizes and unifies the known results that the set of supported solutions is a 2-approximation and that the efficient set itself is a 1-approximation. Moreover, it is shown that, for maximization problems, no approximation guarantee is achievable in general by considering larger ordering cones in the described fashion, which again generalizes a known result about the set of supported solutions.
Keywords: 510; Multiobjective optimization; Approximate Pareto set; Ordering cone; Supported solution; Efficient solution